Sem-Edx And Gc-Ms Analysis Of Phytoconstituents In Anisomeles Heyneana Benth. Leaves From Western Ghats (India) (Applied Biological Research, 2023)
The medicinal herb Anisomeles heyneana Benth is endemic to peninsular  India. In current study the phytoconstituents in the leaves of Anisomeles  heyneana were investigated. The plant material was collected from the  Western Ghats in India. The phytochemicals were extracted from the leaves  by preparing a methanol extract and analyzed using GC-MS and SEM-EDX.  The GC-MS analysis of extract revealed the presence of 22 compounds in it.  These compounds included phenolics, flavonoids, coumarins, glycosides, fatty  acids, terpene and steroids. The predominant compounds in the leaves were  13, 27-cycloursan-3-one (100%), γ-sitosterol (82.04%) and n-hexadecanoic  acid (34.08%). An energy-dispersive X-ray spectrometer (EDS) was employed  to analyse the mass percentage of trace elements. Scanning electron  microscopy showed the presence of carbon, oxygen, sodium, magnesium,  aluminium, silicon, phosphorus, chlorine, calcium, magnesium, and iron. The  carbon was the highest component (48.76 %) as compared with other minerals.
Keywords: Anisomeles heyneana; elemental analysis; GC-MS; SEM-EDX